In-vitro cultivation and biochemical analysis of Pleurotus Ostreatus and Pleurotus Sajor-caju: an approach towards its medicinal properties discovery / Leow Chiuan Herng and Leow Chiuan Yee - Leow, Chiuan Herng; Leow, Chiuan Yee (2008)
In Malaysia, Pleurotus ostreatus (Abalon mushroom) and Pleurotus sajor-caju (Tiram Kerabu mushroom) are most popular as a dietary supplement food. Among the polysaccharides produced by Pleurotus spp., P-l,3-glucans play an important role as biological response modifiers (BRMs). However, most of the biochemical medicinal properties still are not yet found in our Malaysia home-grown Pleurotus sp. In our studies, the mating system was successfully occurred in Pleurotus ostreatus and Pleurotus sajor-caju where new-mated strains were obtained. The best carbon source was starch. Asparagine was the best nitrogen source. B. subtilis was a good nitrogen source but poor carbon source for mycelia growth. Biotin, riboflavin and ascorbic acid were the most suitable vitamins for enhanced the growth of mycelia. Meanwhile, P-1,3- glucan and chitin were also successfully to extract out from the cell wall components for further analysis.